Effects of a Self-Management Program on Health Behaviors ofEmployees at the Electricity Generating Authority of Thailand - Srinukool , Jirapa; Aungwattana , Sivaporn; Boonchiang , Waraporn (Nursing Journal CMU, 2020)
Hypertension is a non-communicable chronic disease that causes premature death. Self-management for changing health behavior reduces the risk of hypertension. This quasi-experimental study aimed to compare the health behavior scores of employees in the pre-and post-programmed care groups, and to compare the health behavior scores between the group receiving the program and the group receiving regular care. The samples were 46 employees of Electricity Generating Authority of Thailand who are at risk for high blood pressure. Their Body Mass Index is equal to 23 kg/square meter. The experimental group included 23 employees, and the control group also included 23 employees. Research instruments used were 1) a self-management program to modify behavior created based on a literature review of hypertension management under the concept of Creer (2000) consisting of six procedures: goal setting, data collection, data processing, decision making, action, and action feedback, 2) a handbook of practice to reduce the risk of hypertension. The total duration was eightweeks, and the instruments used for data collection were 1) general information questionnaire, 2) blood pressure data record and BMI evaluation, and 3) health behavior questionnaire reviewed by three experts. The mean score of health behavior was 0.95 and the reliability of health behavior was 0.83. Descriptive statistics and paired t-test were used in control and experimental groups compared between pre and post tests and t-test after the experiment. The findings indicated that: After participating in the program, the health behavior scores of the employees in the group receiving the program were significantly higher than before (p <.001). After receiving the program, the health behavior scores of the employees in the group receiving the program were significantly higher than the control group (p <.001). It can be concluded that the effect of self-management program is important to help employees to have better health behaviors, reduce the risk of hypertension, and the program can also be used to reduce the risk of other chronic diseases.